La comunidad raizal: elementos para una reflexión jurídica a partir de un discurso étnico. (2012)
The recognition of the ethnic groups by the Colombian Constitution of 1991; accounts for part of multiculturalism discussed by the Constituent Assembly. Since then; Colombia has made significant efforts to issue rules in accordance with constitutional and international principles; seeking the protection of the rights of ethnic communities existing in the country. However; the situation of the actual raizal does not account for this; because although the Constitution recognizes them as an ethnicity; subsequent legislative development does not evidence it. The political participation of native islanders; in its expression as a value; principle and constitutional law; has not been guaranteed just as it happened with other ethnicities.